Direct plasma phosphorization of Cu foam for Li ion batteries. Issue 33 (12th August 2020) - Li, Guoling; Wang, Yuetao; Guo, Heng; Liu, Zhiliang; Chen, Pohua; Zheng, Xinyao; Sun, Junliang; Chen, Hui; Zheng, Jie; Li, Xingguo
Abstract : P is a promising anode material for Li ion batteries, herein, we use plasma activated phosphorous vapor to deposite P on the Cu current collector, which in situ converts the surface of Cu into Cu3 P, leading to a monolithic electrode. Abstract : Phosphorus is a promising anode material for lithium ion batteries, while it suffers from poor electronic conductivity and large volume change during operation. These drawbacks can be effectively overcome by replacing P with Cu3 P, in which Cu serves as a conductive buffer. However, this strategy will cause significant capacity loss due to inclusion of inert Cu. In this work, we use plasma activated phosphorus vapor to deposit P on a Cu current collector, which converts the surface of the Cu into Cu3 P in situ . In this case, the P electrode is converted to a Cu3 P electrode without an external Cu source except for the current collector. The high chemical reactivity of plasma allows phosphorization at only 200 °C, leading to a monolithic electrode with excellent mechanical strength and free of any conductive additive and binder. The obtained electrode exhibits a high initial coulombic efficiency of >90%. The areal capacity is up to 2.3 mA h cm −2 after 50 cycles at 3.2 mA cm −2 .